Comprehensive Echocardiographic Assessment of Ventricular Function and Pulmonary Pressure in the Neonatal Omphalocele Population - Dal Col, Alexis K.; Bhombal, Shazia; Tacy, Theresa A.; Hintz, Susan R.; Feinstein, Jeffrey; Altit, Gabriel (American Journal of Perinatology, 2020)
Objective Pulmonary hypertension (PH) has been described in the neonatal omphalocele population. This study was aimed to describe cardiac function and PH severity using echocardiography in newborns with giant omphalocele (GO) and with non-GO and determine if right ventricular (RV) dysfunction is associated with mortality.Study Design Retrospective, single-center analysis of first echocardiography among neonatal omphalocele patients born between 2004 and 2017 was conducted. Multivariate logistic and univariate Cox's regression was constructed to measure hazard ratio (HR) for death outcome.Results There were 32 newborns, of whom 18 were GO and 7 died. GO had increased systolic pulmonary arterial to systolic systemic blood pressure ratio (97% [isosystemic] vs. 73% [three-fourths systemic] p = 0.03). RV performance parameters (tricuspid annular plane excursion, HR = 0.40; fractional area change, HR = 0.90; and RV peak global longitudinal strain, HR = 1.39) were associated with mortality. These RV performance parameters remained associated in a multiple logistic regression accounting for gestational age and GO status. The overall population had abnormal eccentricity index and pulmonary artery acceleration time to RV ejection time ratio, two markers of PH.Conclusion Patients with omphalocele have increased pulmonary pressure, with GO being worse than non-GO. RV dysfunction at initial echocardiography was significantly associated with mortality.
Keywords: omphalocele; pulmonary hypertension; echocardiography; right ventricular dysfunction; speckle tracking echocardiography